If it's not what You are looking for type in the equation solver your own equation and let us solve it.
f(3)=6(3)-7
We move all terms to the left:
f(3)-(6(3)-7)=0
We add all the numbers together, and all the variables
f3-56=0
We add all the numbers together, and all the variables
f^3-56=0
We do not support efpression: f^3
| -9x+48=3(x-8) | | 9−2z=3 | | 108.18=–9(2d–4) | | (2x+12)+(5x–15)=180 | | C=25+3(p-50) | | -9x+42=3(x-8) | | 16a=18 | | 2k=40 | | x2+110=10 | | 4(u-9)=6u-32 | | 100=75+3x | | X-56=6x=-4 | | 5/4x-17=x-8 | | 16b=64 | | 150=50+2x | | 5k=170 | | 180=3x+2x+80 | | 12x-7=-3x+23 | | 12n-6+6n=12 | | 60=(x+45) | | x2-20=-4 | | 8x—4=6x+2 | | 8x+7=-4x-5 | | 2(3x+5)-2x=0 | | –4z–12=–5z–17 | | 1/2x+1=4 | | 3x-6+1x=2x | | x²+16x+60=0 | | 100=40+40+(2x+30) | | 180=(2x+30) | | 4x=45+15 | | 30=6x5 |